B-cell development and functions and therapeutic options in adenosine deaminase–deficient patients - Brigida, Immacolata (J Allergy Clin Immunol, 2014)
BACKGROUND: Adenosine deaminase (ADA) deficiency causes severe cellular and humoral immune defects and dysregulation because of metabolic toxicity. Alterations in B-cell development and function have been poorly studied. Enzyme replacement therapy (ERT) and hematopoietic stem cell (HSC) gene therapy (GT) are therapeutic options for patients lacking a suitable bone marrow (BM) transplant donor. OBJECTIVE: We sought to study alterations in B-cell development in ADA-deficient patients and investigate the ability of ERT and HSC-GT to restore normal B-cell differentiation and function. METHODS: Flow cytometry was used to characterize B-cell development in BM and the periphery. The percentage of gene-corrected B cells was measured by using quantitative PCR. B cells were assessed for their capacity to proliferate and release IgM after stimulation. RESULTS: Despite the severe peripheral B-cell lymphopenia, patients with ADA-deficient severe combined immunodeficiency showed a partial block in central BM development. Treatment with ERT or HSC-GT reverted most BM alterations, but ERT led to immature B-cell expansion. In the periphery transitional B cells accumulated under ERT, and the defect in maturation persisted long-term. HSC-GT led to a progressive improvement in B-cell numbers and development, along with increased levels of gene correction. The strongest selective advantage for ADA-transduced cells occurred at the transition from immature to naive cells. B-cell proliferative responses and differentiation to immunoglobulin secreting IgM after B-cell receptor and Toll-like receptor triggering were severely impaired after ERT and improved significantly after HSC-GT. CONCLUSIONS: ADA-deficient patients show specific defects in B-cell development and functions that are differently corrected after ERT and HSC-GT.